Dietetic Students' Perceived Facilitators, Barriers and Perceptions of Working with Older Adults: Implications for Curriculum Development. Issue 2 (2nd April 2020) - Jung, Seung Eun; Noh, Hyunjin; Crowe-White, Kristi M.; Ellis, Amy C.
Abstract: Objective: The purpose of this study was to explore dietetic students' facilitators, barriers, and perceptions of working with older adults. Method: A purposive sampling method was used to conduct individual, face-to-face-interviews with students majoring in human nutrition ( n  = 17). All interviews were audio recorded, transcribed verbatim, and coded using NVivo 11 software. A directed content analysis revealed the following themes under categories of (1) perception, (2) barriers, (3) facilitators, and (4) impact of experience. Results: For perception, students discussed older adults' positive and negative personality traits and their physical and cognitive deterioration. Such perception contributed to their view of barriers in interactions with older adults, which were both external and internal in nature. Students mentioned previous experience and knowledge about older adults as well as their own personalities served as major facilitators in interacting with older adults. Gaining experience working with older adults deepened students' understanding of and empathy for this population. Discussion: Findings offer insight into how to develop dietetic curricula to address students' perceptions and resulting barriers for training well-prepared registered dietitians motivated to serve the rapidly growing older adult population.